The Paradox of Feline Coronavirus Pathogenesis: A Review. (21st August 2011) - Myrrha, Luciana Wanderley; Silva, Fernanda Miquelitto Figueira; Peternelli, Ethel Fernandes de Oliveira; Junior, Abelardo Silva; Resende, Maurício; Almeida, Márcia Rogéria de
Abstract : Feline coronavirus (FCoV) is an enveloped single-stranded RNA virus, of the family Coronaviridae and the order Nidovirales . FCoV is an important pathogen of wild and domestic cats and can cause a mild or apparently symptomless enteric infection, especially in kittens. FCoV is also associated with a lethal, systemic disease known as feline infectious peritonitis (FIP). Although the precise cause of FIP pathogenesis remains unclear, some hypotheses have been suggested. In this review we present results from different FCoV studies and attempt to elucidate existing theories on the pathogenesis of FCoV infection.